PEMANFAATAN BIOCHAR UNTUK MENINGKATKAN PRODUKTIVITAS LAHAN KERING BERIKLIM KERING - A. Dariah; N. L. Nurida (Universitas Tribhuwana Tunggadewi, 2012)
Water availability is main constraint to optimalization dry land condition for agriculture development. Therefore innovation technology for water utilization is need. The aims of this study is to determine function of mulch and soil ameandment base of bio-char for improving soil physics, especially for water holding capacity, and to increased productivity and fertilizer efficiency. Filed experiment was conducted in dry land Exp. Station Naibonat, Kupang, during 2010 and 2011. Randomized Block Design was used with three replications. There five treatment was applied such as: control, mulch surface, mulch + soil amandment, vertical mulch, vertical mulch + soil amandment. The result showed that mulch and soil amandment gave significantly effect on growth and yield of Maize. It is also indicated that application of vertical mulch + soil amandment gave a good growth and yield. At extreme condition application mulch and soil amandment did not improve growth and yield of Maize. Application of bio-char as soil amandment in the long-run will improve utilization of organic fertilizer and to support carbon conservation in the soil